Research progress on the role and mechanism of visfatin in sepsis-related organ injury - KUANG Zhong-shen, CONG Zhu-kai, WU Chang-yi, YANG Ning, ZONG Ya-nan, GUO Xiang-yang (Jichu yixue yu linchuang, 2022)
Sepsis is a common acute and critical disease in clinic. Systemic inflammatory response (SIRS) is one of the key mechanisms for the occurrence of sepsis. Visfatin, as an important cytokine, is involved in the occurrence and development of “cytokines storm” caused by sepsis. Recent clinical and basic research have shown that visfatin plays an important role in the occurrence and development of sepsis, and inhibition of visfatin expression can improve the systemic inflammatory response and the damage of lung, heart, liver and other important organs caused by sepsis. Based on the analysis of current clinical and basic research results, visfatin are expected to become an indicator of the severity of sepsis and a potential target for clinical intervention.